Harry's got a girlfriend! - Schubert, Ulli.; Slawski, Wolfgang (New York : North-South, 2000)
Harry is embarrassed to admit that he thinks Michelle is nice, especially when he is the only boy she invites to her birthday party.
Translation of: Hannes geht zum Madchen-Geburtstag!
3.3
K-3
K-3
School Library Journal
310
Keywords: Interpersonal relations -- Fiction; Parties -- Fiction; Interpersonal relations -- Fiction; Parties -- Fiction